1992
DOI: 10.1007/bf00801964
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adriamycin on chronic cardiotoxicity in selenium-deficient rats

Abstract: Adriamycin (doxorubicin) is an antineoplastic drug used to treat various cancers; however, its chronic use is unfortunately accompanied by cardiotoxicity. This toxicity can be reduced by antioxidant agents such as selenium, and it is particularly interesting that cancer patients are usually deficient in this trace element, which suggests that its supplementation could contribute to beneficial treatment. We have examined the effect of adriamycin on chronic cardiotoxicity in 6-week selenium deficiency in rats. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Cancer patients have slightly lower mean selenium levels than do healthy controls (Faber et al , 1995). Several studies have found that selenium deficiency enhances doxorubicin cardiotoxicity in rats (Coudray et al , 1992; Matsuda et al , 1997). In other animal studies, selenium supplementation limited anthracycline‐induced cardiotoxicity by increasing the activity of cardiac mitochondrial GSHPx, reducing the myocardial malondialdehyde content, and abolishing the structural changes of sarcomeres induced by doxorubicin (Boucher et al , 1995).…”
Section: Nutritional Agents For Cardioprotectionmentioning
confidence: 99%
“…Cancer patients have slightly lower mean selenium levels than do healthy controls (Faber et al , 1995). Several studies have found that selenium deficiency enhances doxorubicin cardiotoxicity in rats (Coudray et al , 1992; Matsuda et al , 1997). In other animal studies, selenium supplementation limited anthracycline‐induced cardiotoxicity by increasing the activity of cardiac mitochondrial GSHPx, reducing the myocardial malondialdehyde content, and abolishing the structural changes of sarcomeres induced by doxorubicin (Boucher et al , 1995).…”
Section: Nutritional Agents For Cardioprotectionmentioning
confidence: 99%
“…Of these enzymes, xanthine oxidase is by far the most studied and has been used extensively as a source of superoxide and hydrogen peroxide in vitro. However, a number of studies also indicate that xanthine oxidase is not an important source of free radicals in vivo (Coudray et al, 1992;Rashba et al, 1990;Werns et al, 1991). In vivo, the dehydrogenase form predominates, although conversion to the oxidase form (either by thiol oxidation or proteolysis) occurs under some pathologic situations.…”
Section: Oxidases/peroxidasesmentioning
confidence: 99%
“…In this context, two main groups of studies have been carried out, a first one with those related to selenium deficiency in rats and a second one with the effects of selenium supplementation in several experimental models []. Most authors [], but not all [], reported that selenium as well as GPx‐1 deficiencies lead to an increased doxorubicin cardiotoxicity in rats. These studies mainly concluded that lipid peroxidation, or free radical generation, was involved in the toxic effects occurring in the selenium deficient rats, which through several direct or indirect mechanisms (DNA oxidative damage, mitochondrial alterations, etc.)…”
Section: Impact Of Selenium Intake On the Heartmentioning
confidence: 99%